Bone Chemical Composition Analysis Using Photoacoustic Technique - Feng, Ting; Xie, Yejing; Xie, Weiya; Ta, Dean; Cheng, Qian (Frontiers in Physics, 2020)
Photoacoustic (PA) signal analysis based on ultrasonic wave detection may provide both high-sensitivity optical contrast information and micro-architectural information of tissue. In this study, the feasibility assessment of bone composition assessment was investigated using the multi-wavelength PA analysis (MWPA) method which could reflect the molecular information. By illuminating a bone specimen using a laser light with wavelength over an optical spectrum ranging from 680 nm to 950 nm, the optical absorption spectrum of the bone was acquired. Then, with the optical absorption spectra of all optical absorption chemical components in the known bone, a spectral unmixing procedure was performed to quantitatively assess the relative content of each chemical component. The experimental results from rabbit bones show that MWPA method can be used to assess chemical components related to bone metabolism. Our study confirmed that PA technique can be used as a novel bone diagnostic technique by providing new information about the quantity of bone and identifying biomarkers of bone that can improve the current diagnostic imaging techniques.